THE INFLUENCE OF TEA ROSELLA ON THE DECREASE BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION IN KARANGBOYO VILLAGE CEPU DISTRICT BLORA REGENCY - Vibriani, lntantia; Sutomo, Hadi; Roni, Faishol (WELL BEING, 2016)
At the moment there are so many hypertension sufferers. Traditional medical treatment using herbal plants has been used by society to cope many kinds of health problem, one of them is by using Rosella. This study aims to know the influence of rose/la tea to the decrease of hypertension sufferer blood pressure. This research use one-group pretest- posttest design, it is done by do the pretest with intervention previously, afterwards do the post test. Hypertension sufferers population at Karangboyo village are 64 people, it is used purposive sampling technique so there are 20 people as the sample of this research. The results showed that the average of systolic decrease as 14,2 mmHg and the diastolic decrease as 10,2 mmHg. The data analysis test used paired t test get the number of p value 0,000< α = 0,05, it mean that rosella tea has effect to the decrease of hypertension sufferer blood pressure. From the result above it is expected that the medical staff give information to the society that rosella tea could decrease the blood pressure, so that can decrease the number of high blood pressure. Keywords: hypertension, tea rosella